Miss Nelson is back - Allard, Harry; Marshall, James, 1942-1992 (Boston : Houghton Mifflin, 1982)
When their teacher has to go away for a week, the kids in room 207 plan to "really act up."
3.5
K-3
K-3
Elem. School Library Collection
School Library Journal
Book Links (A.L.A.)
Keywords: Teachers -- Fiction; Schools -- Fiction; Teachers -- Fiction; School stories